Study of Musculoskeletal Disorders in Farmers Involved in Manual Paddy Bagging Task - M.G. Mohamed Thariq; Nathasa Walpita; R.M. Nikzaad; Rahul Jain; Arvind Meena; M L Meena (PT FORMOSA CENDEKIA GLOBAL, 2023)
Filling paddy bags by hand is a common task during harvesting, but it can cause musculoskeletal disorders (MSDs) in various body regions. The current study aims to evaluate posture and find an association between MSDs and body posture scores. The Nordic questionnaire and rapid entire body assessment (REBA) were used to collect MSDs and postures from farmers. The MSD in various body regions (neck, elbows, hands, upper back, knees, ankles, lower back, hips, thighs, and buttocks) was found to be 6.7%, 10%, 3.3%, 6.7%, 16.7%, 20%, and 10%, respectively, during the last 12-month period. In REBA score findings, holding bags, filling the bucket, and the bag were found to have a very high risk of causing MSDs. Despite the fact that MSDs are not very common among farmers who engage in paddy bagging tasks, posture analysis reveals what causes MSDs. Further investigation is needed to improve and reduce MSDs.